Effect of GTAW on the Mechanical Properties of Mild Steel - Elfallah, Saleh Suliman Saleh; Bin Abdullah, Hasan Zuhudi; Binti Idris, Maizlinda Izwana (Journal of Advanced Mechanical Engineering Applications, 2022)
GTAW is considered highly popular in manufacturing. The welding factors such as welding voltage, welding current...etc., play a significant role in determining the welding quality. This study discusses the effect of GTAW factors on the mechanical properties of commercial steel welding. Base metal thickness, welding current and welding speed are factors that will be optimized for maximum tensile strength and hardness using Taguchi’s design. The analysis found that base metal thickness had the highest effect on tensile strength and hardness of the welding, followed by welding current. The welding speed had a lower influence. The optimized combination is the base metal thickness of 10 mm, the welding current of 170A and the welding speed of 100 mm/min